Effects of the fibers distribution in the human eardrum: A biomechanical study - Gentil, Fernanda (2019)
The eardrum separates the external ear from the middle ear and it is responsible to convert the acoustical energy into mechanical energy. It is divided by pars tensa and pars flaccida. The aim of this work is to analyze the susceptibility of the four quadrants of the pars tensa under negative pressure, to different lamina propria fibers distribution. The development of associated ear pathology, in particular the formation of retraction pockets, is also evaluated. To analyze these effects, a computational biomechanical model of the tympano-ossicular chain was constructed using computerized tomography images and based on the finite element method. Three fibers distributions in the eardrum middle layer were compared: case 1 (eardrum with a circular band of fibers surrounding all quadrants equally), case 2 (eardrum with a circular band of fibers that decreases in thickness in posterior quadrants), case 3 (eardrum without circular fibers in the posterior/superior quadrant). A static analysis was performed by applying approximately 3000Pa in the eardrum. The pars tensa of the eardrum was divided in four quadrants and the displacement of a central point of each quadrant analyzed. The largest displacements of the eardrum were obtained for the eardrum without circular fibers in the posterior/superior quadrant.